Solid waste management and contemporary challenges - Silva, Marconi Vieira da; Lopes, Elfany Reis do Nascimento (Revista Nacional de Gerenciamento de Cidades, 2021)
In the present study we analyze and discuss socioenvironmental impacts arising from inadequate management of urban solid waste in the Brazilian Discovery Coast, southern Bahia. We also discuss the challenges to be overcome to promote proper management, highlighting the need for social inclusion of waste pickers. Methodological procedures consisted of an applied and exploratory research, through a review of specialized scientific literature. We also used secondary data available at the Brazilian Institute of Geography and Statistics and at the National Sanitation Information System, and applied a structured online questionnaire to municipal managers of public sanitation services. The cities under study only transfer the waste generated in urban centers to distant areas, in dumps, negatively affecting the environment and public health. There are neither management units nor incentive practices or support programs aimed at recyclable material collectors. Due to the weaknesses and the socioenvironmental, cultural, and historical importance of the area under study, the creation of public policies with broad popular participation is urgently needed to promote a fairer, healthier, and more sustainable development.